I love Lucy. The fifth season [videorecording (DVD)] - Ball, Lucille, 1911-1989; Arnaz, Desi, 1917-1986; Frawley, William, 1887-1966; Vance, Vivian; Asher, William, 1921-2012; Daniels, Marc; Kern, James V., 1909-1966; Carroll, Bob, Jr., 1918-2007; Oppenheimer, Jess; Oppenheimer, Jess (CBS Broadcasting Inc., 2015)
When the Ricardos and Mertzs return from Hollywood, Ricky's band gets booked on an European tour and Fred goes along as the band's manager. Determined not to be left behind, Lucy and Ethel raise the money they need to travel with a charity scam. Europe isn't ready for the new American invasion. Includes all 26 episodes.